SPECTRUM AND TIME-FREQUENCY ANALYSIS TO CHARACTERIZE MICROTREMOR DATA IN SEPAKU SUB-DISTRICT, EAST KALIMANTAN - Rahmania, Rahmania; Diantika, Diantika; Rasmid, Rasmid; Arisalwadi, Meidi; Sastrawan, Febrian Dedi (Indonesian Physical Review, 2024)
Microtremor analysis has been done in the Sepaku Sub-District as a part of the New Capital City of Indonesia. This study aims to determine the characteristics of microtremors in the Sepaku Sub-District using Spectrum Analysis and Time-Frequency Analysis (TFA). Data in this study were taken using a seismometer on the 18 measurement points. The data were processed using default analysis from Geopsy software. Spectrum analysis and TFA used Fourier Transform to change time domain data into the frequency domain. Both analysis ways result in the characteristic microtremor data in the research area. The spectrum analysis data obtained shows two frequency ranges with maximum peaks: middle-frequency (5-8.8 Hz) and high-frequency (11.5-17.6 Hz). Afterward, the TFA shows similar results, where the characteristics of microtremor data are divided into two zones. The maximum peak occurs at the middle-frequency range of 5-10 Hz, and the high frequency ranges above 10 Hz